2013
DOI: 10.5617/jeb.304
|View full text |Cite
|
Sign up to set email alerts
|

Geometric parameters optimization of planar interdigitated electrodes for bioimpedance spectroscopy

Abstract: This paper is concerned with a physical model of an interdigitated sensor working in a frequency range from 100 Hz to 10 MHz. A theoretical approach is proposed to optimize the use of the sensor for bioimpedance spectroscopy. The correlation between design parameters and frequency behavior in coplanar impedance sensors are described. CoventorWare  software was used to model the biological medium loaded interdigital sensor in three dimensions to measure its electrical impedance. Complete system simulation by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 19 publications
1
52
0
1
Order By: Relevance
“…At high frequencies the capacitance resulting from the electrolyte is prevalent. The intermediate range is defined by the resistive characteristics of the electrolyte . In the spectra recorded without electrolyte no differentiation according to the three frequency bands was found.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…At high frequencies the capacitance resulting from the electrolyte is prevalent. The intermediate range is defined by the resistive characteristics of the electrolyte . In the spectra recorded without electrolyte no differentiation according to the three frequency bands was found.…”
Section: Resultsmentioning
confidence: 90%
“…The transducer structures usually consist of finger pairs and gaps, on which a material under test, such as microbiological samples, can be immobilised. Simulations have demonstrated that the detection limit of such structures is mainly driven by the number of electrodes, the finger width and the interspacing distance . These simulations and impedance analyses have revealed that the electrode geometry should be comparable to the size of the target organism .…”
Section: Introductionmentioning
confidence: 89%
“…Performance comparison of the proposed sensor with the interdigitated resistive and capacitive sensors is shown in Table II. The resistance for interdigitated resistive sensor can be written as [11], [12] …”
Section: Resultsmentioning
confidence: 99%
“…This thin layer of particles generates capacitance C dl , while the dielectric capacitance C de represents the overall capacitance of the dielectric medium. Both C dL and R Sol are connected in parallel with the direct capacitive coupling between the electrodes (C Cell ), which depends on the solution dielectric constant and the geometry of the electrodes . The parasitic resistors (R Par ) are generated from the connections and wires of the measuring circuit which is small and can be neglected.…”
Section: Resultsmentioning
confidence: 99%